2012
DOI: 10.1007/978-3-642-33161-9_12
|View full text |Cite
|
Sign up to set email alerts
|

Using NMF for Analyzing War Logs

Abstract: Abstract. We investigate a semi-automated identification of technical problems occurred by armed forces weapon systems during mission of war. The proposed methodology is based on a semantic analysis of textual information in reports from soldiers (war logs). Latent semantic indexing (LSI) with non-negative matrix factorization (NMF) as technique from multivariate analysis and linear algebra is used to extract hidden semantic textual patterns from the reports. NMF factorizes the term-by-war log matrix -that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4
2
1

Relationship

7
0

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…As performance measure, the area under the receiver operating characteristics (ROC) curve (AUC) is used [27][28][29]. To obtain the optimal number of k, the predictive performance of the model as calculated by the cross-validated AUC is optimized [30].…”
Section: Methodsmentioning
confidence: 99%
“…As performance measure, the area under the receiver operating characteristics (ROC) curve (AUC) is used [27][28][29]. To obtain the optimal number of k, the predictive performance of the model as calculated by the cross-validated AUC is optimized [30].…”
Section: Methodsmentioning
confidence: 99%
“…We use text mining methods (e.g. tokenization, case conversion, part-of-speech tagging, stop word filtering, stemming, term weights) to identify keywords [12][13][14]. Based on the keywords, multi-occurrences are identified that are multiple terms that occur more frequently together than it would be expected by chance within a specific term distance [15], [16].…”
Section: Methodsmentioning
confidence: 99%
“…Semantic relationship between terms can be identified by computational techniques that use statistical procedures on eigenvectors (Jiang, Berry, Donato, Ostrouchov, & Grady, 1999;Luo, Chen, & Xiong, 2011). These techniques consider words that are in a project description as well as words that might be in these descriptions (Thorleuchter & Van den Poel, 2012c;Thorleuchter & Van den Poel, 2012d;). LSI is a well-known representative of these techniques.…”
Section: Text Classificationmentioning
confidence: 99%